2011
DOI: 10.1136/ard.2011.154583
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biological agents on work participation in rheumatoid arthritis patients: a systematic review

Abstract: This study reviewed the effect of biological agents on participation in paid work among patients with rheumatoid arthritis (RA). A systematic literature search was performed to identify published articles reporting the effect of biological agents on employment status, sick leave and/or presenteeism. The quality of included articles was assessed according to the guidelines as proposed by the Dutch Cochrane Centre. Narrative summaries were used to present the data separately for randomised controlled trials (RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 33 publications
3
40
0
6
Order By: Relevance
“…The studies exploring the effect of biologic therapy on employment status have produced conflicting results [17], which can partly be explained by differences in study design (i.e., randomised clinical trial (RCT), open-label extension RCT or observational cohort study), inclusion of patients with early or established disease, instrument used to measure employment status, when the assessment of employment status was measured (i.e., prior and after start biologic therapy, at biologic therapy commencement and during follow-up after biologic therapy), follow-up duration, recall period and selection of patient population. For example, in the British Society for Rheumatology (BSR) Biologics Register for RA in the UK (BSRBR-RA), an observational study including patients starting biologic therapy and a control group of patients on sDMARDs, employment status did not differ between patients with RA receiving biologic therapies compared with patients using sDMARDs [18].…”
Section: Absenteeism In Patients Treated With Biologicsmentioning
confidence: 96%
“…The studies exploring the effect of biologic therapy on employment status have produced conflicting results [17], which can partly be explained by differences in study design (i.e., randomised clinical trial (RCT), open-label extension RCT or observational cohort study), inclusion of patients with early or established disease, instrument used to measure employment status, when the assessment of employment status was measured (i.e., prior and after start biologic therapy, at biologic therapy commencement and during follow-up after biologic therapy), follow-up duration, recall period and selection of patient population. For example, in the British Society for Rheumatology (BSR) Biologics Register for RA in the UK (BSRBR-RA), an observational study including patients starting biologic therapy and a control group of patients on sDMARDs, employment status did not differ between patients with RA receiving biologic therapies compared with patients using sDMARDs [18].…”
Section: Absenteeism In Patients Treated With Biologicsmentioning
confidence: 96%
“…Significant reductions in hospitalisation, outpatient physician care, nurse visits and physiotherapy were observed in Sweden between 2001 and 2010 in RA patients relative to the general population 11. A systematic review of 19 studies showed positive effects of biological agents on absenteeism and presenteeism 12. Since long-standing high disease activity, poor functional status and comorbidity are the main cost drivers in RA,13 14 the objective of this study was to analyse how recent changes in treatment and outcomes are reflected in resource utilisation and societal cost.…”
Section: Introductionmentioning
confidence: 99%
“…При переходе к анализу влияния РА на производи-тельность труда пациентов, в той или иной степени сохра-нивших трудоспособность, необходимо напомнить, что су-ществует более полутора десятков инструментов для изуче-ния снижения производительности труда вследствие болез-ни [27], результаты которых мало сопоставимы [27,28]. В нашей работе мы использовали опросник WPAI и не изу-чали динамику производительности труда на фоне различ-ных схем терапии.…”
Section: Discussionunclassified